Pengaruh Pupuk Organik Solid Terhadap Pertumbuhan dan Hasil Tanaman Terung Pada Tanah Podsolik Merah Kuning - Emanuel, Marco; Kardo, Riki; Lela (Hunatech Vol. XXX, No. XXX, 2024)
Green eggplant (Solanum melongena L.) is one of the horticultural products classified as a vegetable with high water and dietary fiber content but low calories, as it contains calcium, protein, fat, carbohydrates, vitamins A, B, and C, phosphorus, and iron. The development of agriculture using red-yellow podzolic soil as a planting medium for eggplants faces several challenges, particularly due to the poor physical and chemical properties of the soil. Efforts to improve the condition of red-yellow podzolic soil (RYP) to make it suitable for the growth and development of eggplants include adding organic matter to the soil. The organic material can be provided in the form of solid organic fertilizer.This study aims to evaluate the effect of solid organic fertilizer on RYP soil for green eggplant growth and to determine the optimal frequency of solid organic fertilizer application on RYP soil for green eggplant growth. The experimental design used was a Randomized Block Design (RBD) with 5 treatments and 4 replications. The treatments consisted of different solid fertilizer doses (X): X0 (control, no treatment), X1 (100 g/plant), X2 (200 g/plant), X3 (300 g/plant), and X4 (400 g/plant). The observed variables included plant height (cm), number of leaves (pieces), number of fruits, and fruit weight (g). The application of solid organic fertilizer yielded positive results for green eggplant production.